Host–Symbiont Interactions in Deep-Sea Chemosymbiotic Vesicomyid Clams: Insights From Transcriptome Sequencing - Lan, Yi; Sun, Jin; Zhang, Weipeng; Xu, Ting; Zhang, Yu; Chen, Chong; Feng, Dong; Wang, Hongbin; Tao, Jun; Qiu, Jian-Wen; Qian, Pei-Yuan (Frontiers in Marine Science, 2019)
Abstract In deep-sea hydrothermal vents and hydrocarbon seeps, chemoautotrophic bacteria use chemical substances as energy resources for primary production, ultimately supporting dense communities of megafauna, including the charismatic giant vesicomyid clams. These clams inherit their endosymbionts from their parents and house them intracellularly in their gills. How these organisms maintain their unique symbiotic relationship at the cellular level, however, remains largely unclear. In the present study, the transcriptomes of different organs in Phreagena okutanii collected from a hydrothermal vent and in Archivesica marissinica collected from a methane seep were sequenced in order to decipher their host-symbiont relationships. Expressional analyses of the transcriptomes showed that the tricarboxylic acid (TCA) cycle-related genes, the Rab gene family, and the lysozyme genes were highly expressed in the gills. Furthermore, genes related to vesicle trafficking, lysosomes, and mitochondrial and energy metabolism were positively selected. The endosymbiont genes involved in sulfur oxidation, oxidative phosphorylation, and adenosine triphosphate (ATP) synthesis were highly expressed. The results suggest that the vesicomyid clams provide intermediates to fulfill the metabolic needs of their endosymbionts, and in return the endosymbionts actively generate nutrients for the hosts through being digested by the lysozymes of the host. Furthermore, the positive selection of genes related to vesicle trafficking, lysosomes, and mitochondrial and energy metabolism indicates the molecular adaptation of the host in order to benefit from symbiosis. Overall, the present study provides the first set of transcriptomes for deep-sea chemosymbiotic vesicomyid clams, facilitating a better understanding of the host-symbiont relationship that has allowed them to become dominant animals in deep-sea hydrothermal vents and cold seeps.